Prioritizing Forestation in China Through Incorporating Biogeochemical and Local Biogeophysical Effects - Yu Li; Pengyi Zhang; Huanhuan Wang; Hui Ma; Jie Zhao; Mengyang Xu; Mengyu Wang; Chenhui Guo; Chao Yue (Earth's Future)
Abstract Forestation is a key strategy for climate mitigation in China through its biogeochemical (BGC) effect of ecosystem carbon sequestration. Additionally, the BGC effect of forestation can be either reinforced or counteracted by concurrent biogeophysical processes (BGP effect) resulting in local land surface warming or cooling, which can be translated into CO2e (i.e., BGC effect) using a local transient climate response. Previous evaluations of the climate mitigation potential of future forestation in China have, however, focused on the BGC effect only and neglected the BGP effect, potentially leading to suboptimal forestation areas. Here, we determined priority forestation areas in China by incorporating both effects to maximize its global climate mitigation effect. Our results suggest an additional 167.2 Mha potentially suitable for forestation in China, exceeding the largest forestation target (86.8 Mha) possibly assumed by the government in 2060. The forestation‐induced BGP effect (18.7 ± 61.9 tCO2e ha−1) largely reinforces the BGC effect (458.2 ± 92.6 tCO2e ha−1) in China, yielding a total climate mitigation effect of 476.9 ± 114.2 tCO2e ha−1 over 40 years (2021–2060). Under the 2060 forestation target, considering both BGC and BGP effects will displace 17.7% (15.3 Mha) of the forestation area derived by considering the BGC effect alone. Integrating both BGC and BGP effects will lead to a CO2 uptake of 28.8 GtCO2e by 2060, 3.9 GtCO2e higher than the value obtained when considering the BGC effect only. Our results highlight the importance of considering BGP effect when making forestation policies for climate mitigation.